M(Other)ing and Care: On the Politics of Caretaking, and Gender - Srivastava, Sonakshi (undercurrents forum für linke literaturwissenschaft, 2024)
Longlisted for the Booker Prize 2020, Avni Doshi’s ’Girl in White Cotton’ makes material the unexpressed concerns and cares in a mother-daughter relationship. Antara finds herself ushered into a new role—that of mothering her mother Tara who is showing early signs of cognitive decline. This role reversal inaugurates a crisis in the personal lives of the estranged duo and leads us to inspect the implications of a pertinent psycho-social issue—that of care-giving as well as care-receiving. The novel toys with the ideas of time, of order, of madness, and the entangled existence of mothers and daughters, and by primarily referencing works of Ira Raja, Rajib Lochan, and Julia Kristeva, I will attempt to understand how the mother-daughter relationship unfolds in the face of a role-reversal—where Antara becomes her mother Tara’s mother.